1994
DOI: 10.1139/z94-099
|View full text |Cite
|
Sign up to set email alerts
|

Lung use and development in Xenopus laevis tadpoles

Abstract: Shortly after hatching, Xenopus laevis tadpoles fill their lungs with air. We examined the role played by early lung use in these organisms, since they are able to respire with both their lungs and their gills. We investigated the effect on X. laevis development when the larvae were prevented from inflating their lungs, and whether early lung use influenced the size of the lungs or the tadpole's ability to metamorphose. Tadpoles that were denied access to air had lungs one-half the size of those of controls. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…However, our tadpoles were only 2-3 days posthatching at the time of landing. Ground-based experiments have shown that Xenopus tadpoles deprived access to air for a period of '12 days immediately after hatching have great difficulty inflating their lungs and ultimately develop lungs half the size of controls (19). Thus, although our experimental tadpoles were functionally indistinguishable from controls 9 days after landing, we cannot conclude that they would have been normal had they spent a longer portion of their posthatching larval life in microgravity.…”
Section: Discussionmentioning
confidence: 63%
“…However, our tadpoles were only 2-3 days posthatching at the time of landing. Ground-based experiments have shown that Xenopus tadpoles deprived access to air for a period of '12 days immediately after hatching have great difficulty inflating their lungs and ultimately develop lungs half the size of controls (19). Thus, although our experimental tadpoles were functionally indistinguishable from controls 9 days after landing, we cannot conclude that they would have been normal had they spent a longer portion of their posthatching larval life in microgravity.…”
Section: Discussionmentioning
confidence: 63%
“…The negative buoyancy in giants, caused primarily by their excessive mass, likely limits proper lung ventilation and leads to their partial solidification. Pronych and Wassersug (1994) showed that the lungs of X. laevis tadpoles that have been denied access to air were substantially smaller and frequently showed anomalies, such as partial solidification. Atkinson and Just (1975) showed that during later metamorphic stages of normal tadpoles there is an increase in the number and size of septa, which potentially increases the surface area of respiratory epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Although tadpoles with lungs that live in normoxic water (meaning water that is 80–100% saturated with dissolved oxygen) usually breathe air, lung respiration is generally not considered essential for tadpole survival (Burggren and Just, 1992; Pronych and Wassersug, 1994; Ultsch et al, 1999). Xenopus tadpoles obtain 17% of their oxygen from air (Feder and Wassersug, 1984) and Rana catesbeiana tadpoles change from 15% at the start of lung use to 80% at the end of climax metamorphosis; lungs are considerably less involved in CO 2 removal than oxygen uptake (Burggren and West, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that lung development and growth are directly affected by the availability of oxygen. Being deprived access to air caused Xenopus tadpoles (Pronych and Wassersug, 1994) and Ambystoma maculatum larvae (Bruce et al, 1994) to develop half-sized lungs, which suggests that lung development also relies upon the physical forces exerted during inflation by air. That lung loss has evolved at least twice in salamanders (Dunn, 1923; Dunn, 1926) and once in each of caecilians and frogs (Bickford et al, 2008; Hutchison, 2008; Nussbaum and Wilkinson, 1995) raises the possibility that plasticity in lung development might allow some normally lunged amphibians to survive without inflating or even developing lungs.…”
Section: Introductionmentioning
confidence: 99%